An analysis of the relationship between quality cues and quality attributes in the purchase of fresh produce by Malaysian consumers - Chamhuri, N.; Batt, Peter (International Society of Horticultural Science, 2011)
Consumers’ preferences and the decision to purchase fresh produce from a retail store are based on a variety of quality cues. In the quality perception process, quality cues are associated with desired quality attributes (values). Malaysian consumers in the Klang Valley most often associate the appearance of the fresh produce (freshness, colour and firmness) with good taste. Fresh fruit and vegetables without any chemical residues, freedom from pests and diseases, and the origin of the produce were suggested as having a strong correlation with food safety and a beneficial impact on the environment and worker welfare. However, the quality cues utilised by consumers to associate fresh fruit and vegetables that taste good, that are safe, and produced in a way that is good for the environment and worker welfare varies significantly between each desired value.